Clinical profile, laboratory predictors, and impact of delayed presentation on disease severity in pediatric acute appendicitis - Naveena Thiagarajan; P. Senthil Kumar; S. Kanagabharathi (International Journal of Contemporary Pediatrics, 2026)
Background: Acute appendicitis is the most common surgical emergency in children, often presenting with variable clinical features leading to diagnostic challenges. Early identification of disease severity is essential to prevent complications. This study aimed to evaluate the clinical profile, laboratory parameters, ultrasonographic findings, and the impact of duration of symptoms prior to presentation on disease severity in paediatric appendicitis. Methods: This hospital-based prospective observational study was conducted over two years in a tertiary paediatric centre. Seventy-five children under 18 years with suspected acute appendicitis undergoing surgery were included. Data on clinical features, laboratory parameters, imaging findings, timing of surgery, and outcomes were analysed using appropriate statistical methods. Results: Among 75 children, 56.0% were males, with most in the 7–12 years age group (54.7%). Simple appendicitis was observed in 68.0% and complicated in 32.0%. Abdominal pain (94.7%) and tenderness (98.7%) were predominant. Ultrasonography identified acute appendicitis in 72.0% and showed significant association with severity (p=0.0005). Complicated appendicitis had higher WBC counts (p=0.001) and lower serum sodium levels (p=0.009). Longer duration of symptoms prior to presentation (3–5 days) was associated with increased complications (50.0%) (p=0.050). Hospital stay was longer in complicated cases (p=0.0005). Conclusion: Clinical evaluation supported by laboratory markers and ultrasonography aids in assessing disease severity. Early presentation and timely management are associated with reduced complications, while delayed presentation increases morbidity in paediatric appendicitis.